India after Gandhi : the history of the world's largest democracy - Guha, Ramachandra (Ecco, 2007)
Born in privation and civil war, divided by caste, class, language and religion, independent India emerged, somehow, as a united and democratic country. This remarkable book tells the full story--the pain and the struggle, the humiliations and the glories--of the world's largest and least likely democracy. Social historian Guha writes of the protests and conflicts that have peppered the history of free India, but also of the factors and processes that have kept the country together (and kept it democratic), defying numerous prophets of doom who believed that it would break up or come under autocratic rule. This story of modern India is peopled with extraordinary characters: Guha gives fresh insights on the lives and public careers of the long-serving prime ministers, but also writes with feeling and sensitivity about the major provincial leaders and other lesser known (though not necessarily less important) Indians--peasants, tribals, women, workers and musicians.--From publisher description.